Rational addiction with optimal inventories: Theory and evidence from cigarette purchases in Japan - Junmin Wan (Osaka University, Institute of Social and Economic Research (ISER), 2005)
A model of rational addiction (RA) with optimal inventories is developed and empirically tested using data on purchases in Japan. If a consumer has information regarding a future price increase, then she may hoard addictive goods; in this case, the optimal inventory period increases with the price hike but decreases with the inventory cost. Owing to the creation of such inventories by consumers, the absolute value of the price elasticity of demand is smaller in the case of a price increase than in that of a price decrease, and this difference is especially salient in the short-run. The evidence provided by daily cigarette purchases is consistent with this asymmetric price effect. Monthly cigarette purchase data do not support the RA hypothesis when inventory is ignored, as inventory becomes an omitted variable that correlates with price; however, this hypothesis does find support if inventory is identified in the demand equation.
Additional information: The Seventh ISER-Moriguchi Prize (2005) Awarded Paper.
Keywords: C12; D11; D12; H31; 330; rational addiction; tax increase; hoarding; optimal stopping; asymmetric price effect; omitted variable; Tabakwaren; Rauchen; Tabaksteuer; Konsumentenverhalten